A comprehensive study of the parameters affecting the stable isotopes in the precipitation of the Bangkok metropolitan area using model-based statistical approaches - Heydarizad M. (2023)
This study determined the main local and regional parameters affecting the stable isotopes (18O, 2H) in the Bangkok precipitation and developed the Bangkok meteoric water line (BMWL) (δ 2H = (7.68 ± 0.07) δ 18O + (7.25 ± 0.48)). First, Pearson correlation coefficients were used to determine the correlation between local and regional parameters. Six different regression methods were used based on Pearson correlation coefficients. The stepwise regression had the most accurate performance among them according to the R2 values. Second, three different methods were used to develop the BMWL, and their performances were also studied. Third, the stepwise regression method was used to study the effects of local and regional parameters on the stable isotope content of precipitation. The results showed that the local parameters had a greater effect on the stable isotope content than the regional ones. The stepwise models developed based on the northeast and southwest monsoons showed that moisture sources also affected the stable isotope content of precipitation. Finally, the developed stepwise models were validated by calculating the root mean square error (RMSE) and R2. This study demonstrated that the local parameters mainly controlled the stable isotopes in the Bangkok precipitation, while the regional parameters had a slight effect on them.